Observer-based Takagi–Sugeno fuzzy sampled-data dynamic positioning controller design for unmanned surface vehicle with external disturbances and actuator faults. (February 2023) - Shi, Jierong; Sun, Haibin; Hou, Linlin
This article investigates the problem of fuzzy sampled-data dynamic positioning output feedback controller design for unmanned surface vehicle with actuator faults and external disturbances. First, the Takagi–Sugeno fuzzy system is established by considering unknown disturbances and actuator faults. Then, a disturbance observer and an extended state observer are proposed to estimate external disturbances, unmeasured states and actuator faults, respectively. Third, based on the outputs of observers, a fuzzy sampled-data dynamic positioning controller is presented to ensure the stability of the closed-loop system. By means of linear matrix inequality technique, the stability conditions are established via the Lyapunov function method. Finally, the simulation result is shown to validate the advantages of the proposed control scheme.